An Underwater Odyssey: The Mission To Image The Wrecks - Woods, Andrew; hutchison, A.; Helmholz, P.; Bickers, A.; Hollick, Joshua (2016)
The opportunity to revisit the wreck sites of HMAS Sydney II and HSK Kormoran was truly a 'once-in-a-career' event. Our aim on the 2015 expedition was to record the two wrecks and their debris fields in immaculate detail. The opportunity to go back was so rare, and so expensive, that we wanted to cover every possible photographic option that we could.